2021
DOI: 10.1186/s12913-021-06573-3
|View full text |Cite
|
Sign up to set email alerts
|

Bypassing primary healthcare facilities for maternal healthcare in North West Ghana: socio-economic correlates and financial implications

Abstract: Background Bypassing primary health care (PHC) facilities for maternal health care is an increasing phenomenon. In Ghana, however, there is a dearth of systematic evidence on bypassing PHC facilities for maternal healthcare. This study investigated the prevalence of bypassing PHC facilities for maternal healthcare, and the socio-economic factors and financial costs associated with bypassing PHC facilities within two municipalities in Northwestern Ghana. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
36
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(44 citation statements)
references
References 30 publications
6
36
2
Order By: Relevance
“…The utilisation of PHLF instead of THLF saves the family 125% of DMC for VD services. This result is consistent with previous studies in Tanzania, 10 12 16 Bangladesh, 5 14 India, 9 17 Ghana, 3 Malawi, 6 Ethiopia, 13 three African countries (Burkina Faso, Kenya and Tanzania), 11 Zambia, 15 Burkina Faso, 22 Vietnam, 23 Pakistan, 24 Afghanistan 25 and the Democratic Republic of the Congo 26 reported that the DMC of VD was higher at a high level or among bypassers compared with low level or non-bypassers. As well as two systematic reviews studies in low-income and middle-income countries.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The utilisation of PHLF instead of THLF saves the family 125% of DMC for VD services. This result is consistent with previous studies in Tanzania, 10 12 16 Bangladesh, 5 14 India, 9 17 Ghana, 3 Malawi, 6 Ethiopia, 13 three African countries (Burkina Faso, Kenya and Tanzania), 11 Zambia, 15 Burkina Faso, 22 Vietnam, 23 Pakistan, 24 Afghanistan 25 and the Democratic Republic of the Congo 26 reported that the DMC of VD was higher at a high level or among bypassers compared with low level or non-bypassers. As well as two systematic reviews studies in low-income and middle-income countries.…”
Section: Discussionsupporting
confidence: 89%
“…Despite the global efforts to improve primary healthcare services, women still tend to bypass the nearby primary reproductive health services (RHS) and it grows frequently in developing countries. 3 4 Previous studies showed that bypassing the primary health level facilities (PHLF) to use the antenatal care (ANC), 3 5–9 vaginal delivery (VD) 3 5–7 9–17 and family planning services 18 at higher levels even if the care available at the nearby PHLF. These studies indicated that the direct medical cost (DMC), direct non-medical cost (DNMC) and indirect costs (INDC) of RHS are different between PHLF and tertiary health level facilities (THLF).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The perceived quality of care is an important determinant of health services use. Perceived quality of care increased the number of women giving birth in health facilities, and women even travelled farther than expected to give birth at facilities, where the quality of care is perceived to be good [ 31 ]. The perceived quality of care further speaks to the issue of ‘respectful maternity care (RMC)’—defined as friendly and woman-centred [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, people in need of a particular service far away from the border might be attracted to a particular service point in a neighbouring unit due to preferred, desirable characteristics. For example, women bypassed the nearest facility in Tanzania, 9 Ghana, 10 Kenya, 11 Mozambique, India and Pakistan. 12 As a result, it is common practice to have childhood immunisation coverage from routine data greater than 100% in administrative units that attract many people from neighbouring administrative units.…”
Section: Modest Approaches Used To Define Service Catchment Areasmentioning
confidence: 99%